Risk management and funds distribution in mosque institution at Puncak Alam / Muhammad Asyran Mohd Aseri. - Mohd Aseri, Muhammad Asyran (2019)
Mosque is one of important institution in Islam which not only a place to perform salah (prayer) but it is the centre of the Islamic community that can have a huge impact on the Muslim or non-Muslim community in the area. In achieving the objective that impacts the community, the management of the mosque institution should be effective which include issues in risk management and fund collection and distribution are effectively addressed. This study is conducted to examine the management of fund collection and distribution with the main objective to analyse the risk management practices of mosque institution in Puncak Alam. The design of this study was restricted to the use of the qualitative experimentation methods, which focuses on the members and mosque management committee. I hope this research will give a very good impact to the society and mosque institute in Puncak Alam to improve their management and finally give more good impact to community in Puncak Alam area.